Some Novelties in Classification and Analysis of Facebook data – A Decision Tree based Approach - et. al., Prashant Bhat , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As of 2020 statistics, Facebook is the huge social media platform universally having 2.6 billion monthly active users all over and generates data in petabytes every day. Hence Knowledge Discovery from such a huge data is very essential. At present days, Knowledge Discovery is a significant research area. To get the ultimate answers for many research questions in data mining, the final hope is knowledge that can be achieved from different forms of data. If the data has known associations or the data is labelled, supervised approach i.e., Classification method can be used. To accomplish this task, we propose a novel approach to classify the Facebook data at most accuracy.